Response to metals treatment of Fra1, a member of the AP-1 transcription factor family, in P. lividus sea urchin embryos. (August 2018) - Russo, Roberta; Bonaventura, Rosa; Chiaramonte, Marco; Costa, Caterina; Matranga, Valeria; Zito, Francesca
Abstract: Lithium (Li), Nickel (Ni), and Zinc (Zn) are metals normally present in the seawater, although they can have adverse effects on the marine ecosystem at high concentrations by interfering with many biological processes. These metals are toxic for sea urchin embryos, affecting their morphology and developmental pathways. In particular, they perturb differently the correct organization of the embryonic axes (animal-vegetal, dorso-ventral): Li is a vegetalizing agent and Ni disrupts the dorso-ventral axis, while Zn has an animalizing effect. To deeply address the response of Paracentrotus lividus embryos to these metals, we studied the expression profiling of Pl-Fra transcription factor (TF), relating it to Pl-jun, a potential partner for AP-1 complex formation, and to Pl-MT, known to be an AP-1 target and to have a protective role against heavy metals. The AP-1 TFs are found throughout the animal kingdom and are involved in many cellular events, i.e. cell proliferation and differentiation, immune and stress responses, cancer growth. Here, we isolated the complete Pl-Fra cDNA and showed that Pl-Fra transcript, already present in the unfertilized eggs, was newly synthesized from the blastula stage, while its spatial distribution was mainly observed in skeletogenic cells, similarly to Pl-jun . Interestingly, Pl-Fra expression was induced by the different metals and the induction kinetics revealed its persistent expression during treatments. Moreover, its temporal and spatial behavior in response to the three metals was comparable to that of Pl-jun and Pl-MT . The understanding of AP-1 functions in invertebrates may provide new knowledge about the mechanisms of response to metal injuries, as well as it might lead to acknowledge the TFs as new type of biomarkers for the evaluation of hazards in polluted environment. Highlights: Pl-Fra is a newly isolated member of AP-1 family. Pl-Fra and Pl-jun are responsive to Li, Ni, Zn injuries. Induction kinetics of Pl-Fra and Pl-jun reveal their persistent expression during metal treatments.